Experimental investigations on thermal properties of nano-SiO2/paraffin phase change material (PCM) for solar thermal energy storage applications. Issue 19 (1st October 2020) - Manoj Kumar, P.; Mylsamy, K.; Saravanakumar, P.T.
ABSTRACT: This paper investigates the influence of low mass% SiO2 nanoparticles on the thermal properties of the paraffin wax for solar thermal energy storage applications. The four nano-SiO2 /paraffin PCM samples containing, 0.0 mass%, 0.5 mass%, 1.0 mass%, and 2.0 mass% of SiO2 nanoparticles in paraffin wax were synthesized. The prepared nano-SiO2 /paraffin PCMs were investigated with different experimental techniques to assess their thermal properties and physical structure. The analysis evidenced that the fusion of SiO2 nanoparticles with paraffin wax was homogeneous, and they enhanced the thermal conductivity of paraffin wax to 12.78%, 22.78%, and 33.34%, respectively, with the aforementioned mass% of SiO2 nanoparticles. Likewise, the dispersion of SiO2 nanoparticles prolonged the thermal degradation of paraffin wax without disturbing its chemical structure and also altered the melting and solidification temperature of the paraffin in a favorable manner. However, the latent heat of the paraffin wax was decreased with the increasing mass% of the nanoparticles and decrement is noteworthy for more than 1.0 mass% of SiO2 nanoparticles in paraffin wax. Altogether, the outcomes revealed that the enhancement of thermal properties were significant, when paraffin wax is supplemented with lowest mass% of SiO2 nanoparticles and to be appropriate for enhanced thermal energy storage.